2023
DOI: 10.1186/s13256-023-04121-7
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal liposarcoma: a case report and review of the literature

Jamal Ataya,
Ali Alakbar Nahle,
Hussein Hamdar
et al.

Abstract: Background Mediastinal Liposarcoma (ML) is an exceedingly rare neoplasm, accounting for less than 1% of all liposarcomas. Surgical resection is the most effective therapeutic modality, while adjuvant radiation therapy may be recommended for unresectable tumors. Case presentation This case report presents a rare case of a 52-year-old Syrian male patient with well-differentiated mediastinal liposarcoma (ML) who presented with exertional dyspnea, coug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…1 El liposarcoma mediastinal crece de manera silente, engloba vasos sanguíneos, corazón y órganos vecinos, 2 y conduce a la presentación de manifestaciones clínicas cuando es gigante. 3 La tomografía del tórax con contraste suele ser la mejor herramienta para diagnosticar y diseñar la cirugía. 4 Puede complementarse con resonancia magnética del tórax, angiotomografía, eventualmente PET scan para la caracterización del tumor y la extensión de enfermedad.…”
Section: Discussionunclassified
“…1 El liposarcoma mediastinal crece de manera silente, engloba vasos sanguíneos, corazón y órganos vecinos, 2 y conduce a la presentación de manifestaciones clínicas cuando es gigante. 3 La tomografía del tórax con contraste suele ser la mejor herramienta para diagnosticar y diseñar la cirugía. 4 Puede complementarse con resonancia magnética del tórax, angiotomografía, eventualmente PET scan para la caracterización del tumor y la extensión de enfermedad.…”
Section: Discussionunclassified
“…Macroscopically, DDLPs are usually large-sized, multinodular, yellow, solid masses. Taking into consideration the review of Ataya et al, who reported 11 patients with giant tumors equal to or greater than 20 cm and 13 patients with tumors equal to or greater than 10 cm, it is important to mention that mediastinal liposarcomas can obtain a substantial size before becoming symptomatic [ 7 ]. Mediastinal liposarcomas usually arise from the posterior mediastinum, followed by the anterior, as in our patient, and, most rarely, the middle compartment of the mediastinum [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…DDLPs constitute an entity with vague clinical and histopathological characteristics, as well as poor data regarding prognosis and outcome due to their rarity, especially when originating from the mediastinum compartments [ 7 ]. Clinical presentation is non-specific and delayed diagnosis is common due to low-rate growth, leading to symptoms due to tumor invasion and compression of adjacent organs [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lipoma is an encapsulated tumor composed predominantly of fat and contains small blood vessels. Liposarcomas also comprise predominantly fatty tissues but contain varying amounts of soft tissue and may show some aggressive features such as local invasion, locoregional lymphadenopathy and distant metastasis [25,46,47]. Seminomas and nonseminomatous germ cell tumors (NSGCT), comprising embryonal carcinoma, choriocarcinoma, yolk sac tumor, mixed germ cell tumors and teratoma with malignant transformation, are malignant germ cell tumors that occur almost exclusively in young men between the ages of 20 to 40 years.…”
Section: Germ Cell Tumorsmentioning
confidence: 99%